Enhancing Students Learning Outcomes and Creative Thinking Skills in Computer Numeric Control Subject Using Project-Based Learning Model - Elly Rahmawati; Supari Muslim; Soeryanto Soeryanto; Tri Rijanto (Universitas Ahmad Dahlan, 2021)
This study aimed to determine the effect of project-based learning on student learning outcomes and creative thinking skills in computer numeric control subjects at SMK KAL-1 Surabaya. This study used a quasi-experimental factorial research design with a 2-way ANOVA test technique. In this study, 66 students from class XI of the Mechanical Engineering Expertise Program were divided into experimental groups (n= 33) and a control group (n= 33). The instrument used in this research is in the form of test sheets and observations to measure the level of students creative thinking and their learning outcomes. This study found that student learning outcomes using project-based learning are significantly higher than students who taught using direct learning models in computer numeric control subjects. Furthermore, the learning outcomes of students who have a high level of creative thinking are significantly higher than those of students who have a low level of creative thinking. Moreover, there is an interaction between using learning models and creative thinking on three domains of learning outcomes (cognitive, affective, and psychomotor) in computer numeric control subjects.